Tailored versus Standard Dose Prophylaxis in Children with Hemophilia A - Santoro, Cristina; Baldacci, Erminia; Mercanti, Caterina; Mazzucconi, Maria Gabriella (Seminars in Thrombosis and Hemostasis, 2013)
Prophylaxis is universally recognized as the treatment of choice in people with hemophilia, and tailored prophylaxis is the consistent modification of the standard weight-based dosing regimen. A large number of factors guide the choice of a specific tailored regimen, and different regimens are under evaluation. Tailored low-dose frequent regimens are likely to be cost-effective, but they are less accepted by patients. Escalating dose regimens seem to be quite effective in preventing bleedings and, consequently, arthropathy, although data on long-term outcomes are still not available. Pharmacokinetic-driven approaches have been also proposed. Sensitive and validated tools able to reliably measure the different outcomes are necessary in this setting. With regard to the evaluation of arthropathy, magnetic resonance imaging and ultrasound are promising imaging techniques in detecting early joint damage. Factor VIII trough levels can be considered a measure of the efficacy of FVIII infused, although other factors influence the bleeding pattern. Global assays of coagulation could provide more complete information on the hemostatic potential of a sample and predict bleeding phenotype. These techniques are also promising for the individualization of prophylaxis regimens, potentially resulting in less frequent dosing, more comfortable and less expensive approaches.
Keywords: hemophilia A; tailored prophylaxis; children; standard prophylaxis; outcomes